2015
DOI: 10.5194/hess-19-4673-2015
|View full text |Cite
|
Sign up to set email alerts
|

Reconciling high-altitude precipitation in the upper Indus basin with glacier mass balances and runoff

Abstract: Abstract. Mountain ranges in Asia are important water suppliers, especially if downstream climates are arid, water demands are high and glaciers are abundant. In such basins, the hydrological cycle depends heavily on high-altitude precipitation. Yet direct observations of high-altitude precipitation are lacking and satellite derived products are of insufficient resolution and quality to capture spatial variation and magnitude of mountain precipitation. Here we use glacier mass balances to inversely infer the h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

27
319
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 287 publications
(347 citation statements)
references
References 60 publications
(83 reference statements)
27
319
1
Order By: Relevance
“…In the far west of the HKH, a unimodal pattern of cyclonic winter precipitation can be found on the northern side of the Hindu Kush (Schiemann et al, 2008). The advection of differing air masses results in variable temperature lapse rates and, in some areas, seasonal precipitation regimes differing between arid valley bottoms, where most meteorological stations are situated, and adjacent high-elevation areas with ample precipitation (Hewitt, 2014;Immerzeel et al, 2015).…”
Section: Climate and Climate Change In The Hkhmentioning
confidence: 99%
See 1 more Smart Citation
“…In the far west of the HKH, a unimodal pattern of cyclonic winter precipitation can be found on the northern side of the Hindu Kush (Schiemann et al, 2008). The advection of differing air masses results in variable temperature lapse rates and, in some areas, seasonal precipitation regimes differing between arid valley bottoms, where most meteorological stations are situated, and adjacent high-elevation areas with ample precipitation (Hewitt, 2014;Immerzeel et al, 2015).…”
Section: Climate and Climate Change In The Hkhmentioning
confidence: 99%
“…Furthermore, snowfall measurement is inherently difficult, with errors often in the range of 20-50 % undercatch (Rasmussen et al, 2012). Satellite-derived products such as the Tropical Rainfall Measuring Mission (TRMM) provide gridded precipitation in data-sparse regions but likely with reduced quality for snowfall and in high-elevation terrain (Derin et al, 2016;Immerzeel et al, 2015;Yin et al, 2008). As a consequence, gridded climate data are poorly characterized in the HKH (Bao and Zhang, 2013;Ménégoz et al, 2013;Xie et al, 2007), especially at high elevation, and corresponding maps (including Fig.…”
Section: Climate and Climate Change In The Hkhmentioning
confidence: 99%
“…A new historical precipitation dataset [52] that corrects for the underestimation of high altitude precipitation is used.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the Karakoram Range received maximum precipitation at an elevation of above 5500 m, whereas high elevation (4000 m) regions generate much of the UIB's flow [5,8]. However, only a few studies, e.g., [9,10] have monitored the climatic parameters, snow and ice processes and resultant hydrological regimes at these altitudes.…”
Section: Introductionmentioning
confidence: 99%
“…In remote regions, such as the UIB, satellite remote-sensing techniques may be the only way to analyze spatiotemporal variations in snow cover [2,31]. Moderate Resolution Imaging Spectroradiometer (MODIS) snow products have been widely used in estimating the spatial extent of snow cover and in snowmelt runoff modeling applications [2,9]. Several studies have compared the relatively "coarse" resolution (500 m) MODIS data with the "fine" resolution (30 m) Advanced Spaceborne Thermal Emission and Reflection Radiometer (ASTER) data and ground observations in estimating snow cover; the MODIS presented satisfactory results at both low and high altitudes [2].…”
Section: Introductionmentioning
confidence: 99%